Outcome analysis of post reduction pauwels angle in fracture neck of femur treated with dynamic hip screw or 6.5 mm cancellous cannulated screw fixation - Ajit Ganvir; Ashish Sirsikar; Sameer Gupta (International Journal of Medical Research and Review, 2015)
Introduction: Fracture within the neck region of intracapsular area of hip known as fracture neck of femur. Radiologically breakage in shenton’s line is diagnosed as a fracture of neck of femur. Still this fracture remains an enigma to the Orthopaedic surgeon and is called as unsolved fracture.Aim of study: This study is undertaken to assess the correlation between post reduction Pauwel’s angle and union rate in the fracture neck of femur treated with either Dynamic Hip Screw or Cannulated Cancellous Screw fixation.Materials and Methods: This was a prospective study from June 2006 to October 2008. The study included 48 patients who underwent Dynamic Hip Screw and Cannulated Cancellous Screw fixation for fracture neck of femur.Results: This study evaluated Post reduction Pauwel’s angle for both types of fixation. Data analysis showed that with rise in Post reduction Pauwel’s angle, union rate decreases in both types of fixation.Conclusion: Post reduction Pauwel’s angle is a good guide to know the stability of fractures and decrease in this angle corrects shearing instability of the fracture site. This study gives an indication that with a vertical fracture line, a valgus osteotomy might help in decreasing the incidence of non union.